DOES THE PRESENCE OF STRAW IN THE BILLET AFFECT THE QUALITY OF SUGARCANE PLANTING SYSTEMS? - Frazão,Aycon T. L. (2019)
ABSTRACT The mechanized harvesting process of sugarcane seedlings affects the mechanized planting operation in the sense that straw adhered to the billet can reduce the quantity of non-viable gems obtained as a result of mechanical damage sustained during the mechanized operation. This study proposes a method to improve the quality of the implantation of sugarcane crop by prevention of damages caused mainly during October/November, when adverse climatic conditions of higher water stresses and high temperatures exist. The objective of this study is to evaluate the quality of the sugarcane planting operation using seedlings with and without straw, distributed by planters and distributors of chopped sugarcane, and comparing their performance to that of semi-mechanized planting. The study was conducted at Fazenda Santa Clara, located in Pradópolis - São Paulo, Brazil and considered five processes: mechanized planting of seedlings without straw, mechanized planting of seedlings with straw, mechanized distribution of seedlings without straw, mechanized distribution of seedlings with straw, and semi-mechanized planting. Fifty sample points were used to collect data for each process, as per the principles of Statistical Process Control. The number of unfeasible gems and faults in the stand reduced with the presence of straw in the grinding wheel, in addition to less variability being presented. The presence of straw in the billet enabled the best overall quality of sugarcane plantation.